Non-local thermodynamic equilibrium analysis of the methylidyne radical molecular lines in metal-poor stellar atmospheres - Popa, Silvia Anastasia; Hoppe, R.; Bergemann, Maria; Hansen, Camilla Juul; Plez, B.; Beers, T. C. (Astronomy and astrophysics, 2023)
Aims. An analysis of the methylidyne (CH) radical in non-local thermodynamic equilibrium (NLTE) is performed for the physical conditions of cool stellar atmospheres typical of red giants (log ɡ = 2.0, Teff = 4500 K) and the Sun. The aim of the present work is to explore whether the G band of the CH molecule, which is commonly used in abundance diagnostics of carbon-enhanced metal-poor stars, is sensitive to NLTE effects. Methods. LTE and NLTE theoretical spectra were computed with the MULTI code. We used one-dimensional (1D) LTE hydrostatic MARCS model atmospheres with parameters representing eleven red giant stars with metallicities ranging from [Fe/H] = −4.0 to [Fe/H] = 0.0 and carbon-to-iron ratios of [C/Fe] = 0.0, +0.7, +1.5, and +3.0. The CH molecule model was represented by 1981 energy levels, 18 377 radiative bound-bound transitions, and 932 photo-dissociation reactions. The rates due to transitions caused by collisions with free electrons and hydrogen atoms were computed using classical recipes. Results. Our calculations suggest that NLTE effects in the statistical equilibrium of the CH molecule are significant and cannot be neglected for precision spectroscopic analysis of C abundances. The NLTE effects are mostly driven by radiative over-dissociation, owing to the very low dissociation threshold of the molecule and significant resonances in the photo-dissociation cross-sections. The NLTE effects in the G band increase with decreasing metallicity. When comparing the C abundances determined from the CH G band in LTE and in NLTE, we show that the C abundances are always under-estimated if LTE is assumed. The NLTE corrections to C abundance inferred from the CH feature range from +0.04 dex for the Sun to +0.21 dex for a red giant with metallicity [Fe/H] = −4.0. Conclusions. Departures from the LTE assumption in the CH molecule are non-negligible, and NLTE effects have to be taken into account in the diagnostic spectroscopy based on the CH lines. We show here that the NLTE effects in the optical CH lines are non-negligible for the Sun and red giant stars, but further calculations are warranted to investigate the effects in other regimes of stellar parameters.